Phyllostomidae assemblage (Chiroptera: Mammalia) in altitudinal forests at the Parque Estadual do Ibitipoca, Southeast of Minas Gerais, Brazil - Mello,Rodrigo M. (2016)
ABSTRACT Many studies have demonstrated the ecological relevance and great biodiversity of bats in Brazil. However, mountainous areas have been disproportionately less sampled, mainly in the Southeast. The aim of this study was to identify and compare the richness and diversity of Phyllostomidae, the most diverse bat family, in different forest types in Parque Estadual do Ibitipoca, trying to understand the causes of possible differences. The Parque Estadual do Ibitipoca is inserted in the Serra da Mantiqueira's domain, in an Atlantic Forest region known as "Zona da Mata", state of Minas Gerais, with an altitudinal range between 1200-1784 meters. The study was conducted in two forest types, classified as "Nanofloresta Nebular" and "Floresta Nebular", whose respective data on richness and diversity were compared. The bats were captured with 8-10 mist nets for 14 months (April 2011 to May 2012) and four nights per month totaling 62,171.25 m2h of capture effort. A total of 392 captures (12 species) belonging to the Phyllostomidae family were obtained. The most abundant species were Sturnira lilium (59.9%), Platyrrhinus lineatus (11.3%), Artibeus lituratus (8.7%) and Carollia perspicillata (7.6%). The two sampled areas presented differences in bat richness, diversity and species composition, and this difference was predominantly influenced by S. lilium. It is likely that the observed difference in the assembly of bats between the two study sites depends on the variation in floristic composition. The records of A. lituratus and P. lineatus in a few months of the year and close to Ficus mexiae bearing ripe fruits suggests that at least these species move to the park for a few periods of the year in search of food resources, possibly moving through the altitudinal landscapes.